A novel poly(ethylene glycol)–grafted poly(arylene ether ketone) blend micro-porous polymer electrolyte for solid-state electric double layer capacitors formed by incorporating a chitosan-based LiClO4 gel electrolyte. Issue 46 (11th November 2016) - Na, Ruiqi; Huo, Guanze; Zhang, Shuling; Huo, Pengfei; Du, Yinlong; Luan, Jiashuang; Zhu, Kai; Wang, Guibin
Abstract : A novel PAEK/PAEK- g -PEG blend MPE with a chitosan-based LiClO4 gel electrolyte was prepared and applied in an S-EDLC. Abstract : A novel strategy was used to prepare a high performance micro-porous polymer electrolyte (MPE) from a poly(arylene ether ketone) (PAEK)/poly(ethylene glycol) grafted poly(arylene ether ketone) (PAEK- g -PEG) polymer composite membrane matrix incorporating a chitosan based LiClO4 gel electrolyte. The morphology, porosity, and thermal and mechanical properties of the PAEK/PAEK- g -PEG polymer blend membrane matrix were investigated. To improve the liquid retention capacity of the MPE, a simple but effective method involving the addition of chitosan was implemented. The effects of chitosan concentration on the liquid uptake and leakage behaviors as well as the ionic conductivity of the electrolyte were also evaluated. The synthesized MPE exhibited an ionic conductivity as high as 8 × 10 −3 S cm −1 at room temperature. More importantly, a novel solid-state electric double layer capacitor (S-EDLC) could be fabricated using the synthesized MPE and activated carbon electrodes. For comparison, an EDLC was also assembled using the corresponding aqueous electrolyte and a commercial separator (NKK-MPF30AC-100). Alternating current (AC) impedance measurement results showed that the interfacial compatibility of the MPE and the activated carbon electrodes was high. Meanwhile, the as-prepared S-EDLC showed a specific capacitance of 118.63 F g −1, with an energy density of 7.87 W h kg −1 and power density being 95.97 W kg −1 at a current density of 1 A g −1 . Furthermore, the S-EDLC exhibited greater cell-cycling stability after 5000 charge/discharge cycles than did the EDLC, indicating that this novel MPE should be suitable for use in EDLCs and other energy storage systems.